Retrofit of Control Active Roll Damping System at KRI RUPAT 712 using PLC OMRON CJ2M CPU 31 - Surawan Setiyadi (Journal of Electrical And Electronics Engineering, 2019)
Minesweeper Warship KRI Pulau Rupat 712 needs stability when sails at the sea. Stability control system has had some problems due to their electronic life time equipment, remembering that this ship was made by Holland in 1984 (more than 30 years ago). Rejuvenation of control system is needed in order that its stability system is still can be functioned. Current control system use electronics card which is rather difficult to be repaired when it is broken. PLC is one of the solutions to change the electronics card system because PLC is easy to install and using programming system which is also easy to learn and having been used by a lot of industry likes automotive, food and beverage, oil and gas, textile, and etc. Some of the old instruments still can be used because PLC can support them, except there are few instruments that must be changed and added, for example: must change the gyro sensor and add the soft button HMI to change the hard button.